Students’ Perceptions of Teacher’s Approaches: Traditional Versus Interactive Teaching Media - Mustofa, Aritmatika Fayzha; Hanafi, Muhamad; Khotimah, Khusnul (ICONELT, 2024)
This study highlights the importance of incorporating interactive teaching media to enhance student engagement and learning outcomes in language education. Using a qualitative method and case study approach, data were collected through open-ended questionnaires from seven participants. This study explores 7th-grade students’ perceptions of traditional teaching media versus interactive teaching media, specifically focusing on manual scramble word games. Findings reveal a strong preference for the scramble word game, with students citing its enjoyment, engagement, and effectiveness for learning English vocabulary. The result obtains a positive impact of the scramble word game beyond mere enjoyment; it also enhances students’ motivation to learn and improves their comprehension of English vocabulary. Despite some minor challenges reported by a few participants, the overall consensus favors using interactive teaching methods for language learning.